Analisis Kesuksesan Website E-Learning Management System (EMS) Dengan Menggunakan Model Delone dan McLean Pada Cabang Primagama Bumi Citra Fajar (BCF) - Marselia, Selly; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Primagama has several advantages, one of which is the use of E-Learning Management System (EMS). EMS is a platform for online national or school try out exam exercises as well as other computer-based exams. Based on the results of the initial questionnaire of 40 primaga students, still a lot of students approximately around the 37.5% who rarely use EMS website or not even using other menus optimally. Furthermore, during implemented, this website has never been evaluated towards the system quality, information quality, and service quality. Based on the problem above, it is necesssary to analyze the success of the E-Learning Management System (EMS) website in Primagama BCF Sidoarjo branch by using Delone & McLean Information Systems Success Model. This model has 6 (six) dimensions i.e. system quality, information quality, service quality, usage, user satisfaction, and net benefits. The results of the research with the 87 samples indicate that the usage variable very positively affect the net benefit approximately 99,8%, and service quality variable positively affect the usage approximately 20,4%, which means, in increasing the success of EMS website it is necessary to improve the service quality and the usage so that the website is useful. The given recommendations i.e. 1) The appearance of the website should be attractive, readable text, good image quality with small size, use nice and simple color. 2) The content must be brief, solid, and clear, content should be updated regularly, and interact/interactive. 3) The function of each component should work correctly quick, avoid grammatical, spelling, or writing errors. 4) Usability, the website should be easy to operate, simple, quick loading times, and consistent layout. Keywords: Primagama, Delone and McLean, E-Learning Management System